Swettenham Pier waterfront redevelopment, Penang - Ismail, Sumarni; Teoh, Tong M.; Yusoff, Sarizal Yusman; Utaberta, Nangkula; Mohd Yunus, Mohd Yazid; Ismail, Nor Atiah (American-Eurasian Network for Scientific Information, 2015)
A waterfront is a place where life of a city bloomed. Water is the source of life. Life is the practice of living. A waterfront signified a city's growth, bounded by water. Swettenham Pier is one part of Penang Island's east coast waterfront link, and happened to be at the sport where Georgetown started. The spot where in history, Sir Francis Light landed on this island and where Georgetown is established along with the blooming of international entrepot activities. It was glorious back in the late 80's. The main objective of this thesis is to bring back the glory moment of Swettenham Pier, giving back the waterfront to the people of Georgetown, people of Penang. Having to attend to this said aim, the redevelopment of Swettenham Pier waterfront is to give a chance to the people to claim a part of this waterfront, for living, for leisure or for any unplanned activities, as to establish its aim to contribute back to the local people, local culture and local living. This call for a strategy to design a waterfront to revive the history, while injecting new life to the place for people and activities to be carry on care freely. The design potential of this project is to look through the entire master plan of the waterfront and then move into the micro elements that support the entire scheme. The master plan plays a crucial role in supporting the waterfront with various types of activities that serve various demographics of users. The redevelopment of the new cruise terminal would also be explored thoroughly in conjunction with Penang Structure Plan in order to come out with the design that could cope with future development. One of the key outcomes of this research is that community magnet or a civic component inserted in the scheme will contribute back to the local people and culture.